THE LEMON TREES AND THE SYRIAN HOMELAND: AN ECOCRITICAL READING OF ZOULFA KATOUH’S AS LONG AS THE LEMON TREES GROW - Latumeten, Anna Anganita Theresia; Nofansyah (Faculty of Letters Universitas Balikpapan, 2024)
This descriptive qualitative study aims to analyze Zoulfa Katouh’s As Long as the Lemon Trees Grow from an ecocritical perspective, focusing on how the natural environment is central to the narrative. By applying ecocriticism, this paper demonstrates how the novel's themes of home, identity, and surviv-al are deepened, particularly in contemporary war narratives. The enduring presence of the natural world encapsulates the overarching message of the novel: hope—like nature—is resilient. Furthermore, it is crucial to recognize that during times of war, human trauma is not the only impact; the environ-ment is significantly affected as well. As Long as the Lemon Trees Grow highlights the complex relationship between nature and human resilience in wartime, emphasizing that the survival of the land is intertwined with the sur-vival of its people. This analysis contributes to a deeper understanding of the novel's ecological dimensions and the broader implications of nature's role in shaping human experience amidst conflict.